2019
DOI: 10.1002/mc.22951
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone sensitizes human pancreatic cancer cells to EGFR inhibitors through the inhibition of STAT3 signaling

Abstract: Several studies have implicated the feedback activation of signal transducer and activator of transcription 3 (STAT3) as a new cancer drug-resistance mechanism and linked it to the failure of epidermal growth factor receptor (EGFR)-targeted therapies.In this study, we discovered that Alantolactone, a natural sesquiterpene lactone, potently inhibited human pancreatic cancer cells and suppressed constitutively activated STAT3. In contrast, Alantolactone had little effect on the EGFR pathway.Moreover, combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 40 publications
1
46
1
Order By: Relevance
“…alT is the main biologically active compound derived from Inula helenium (42). alT has been widely researched as a potential candidate for the treatment of several types of cancer, and previous in vivo studies have reported its antiproliferative, anti-metastatic and anti-invasive activity in a variety of cell lines (19,20,42). The present study aimed to evaluate the effect of alT on osteosarcoma and to determine whether it could be used as a potential future treatment strategy for this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…alT is the main biologically active compound derived from Inula helenium (42). alT has been widely researched as a potential candidate for the treatment of several types of cancer, and previous in vivo studies have reported its antiproliferative, anti-metastatic and anti-invasive activity in a variety of cell lines (19,20,42). The present study aimed to evaluate the effect of alT on osteosarcoma and to determine whether it could be used as a potential future treatment strategy for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that alT promotes numerous biological effects, including anti-inflammatory and antioxidant functions (18,19). it has also been observed to suppress several types of human cancer, including gastric, pancreatic and breast cancer cells (19)(20)(21). it is reported that these anticancer effects of alT are mediated through the Pi3K/aKT signaling pathway (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al stated that ALT may improve the therapeutic e ciency of the chemotherapeutic drug oxaliplatin [10]. Zheng et al demonstrated that ALT could sensitize human pancreatic cancer cells to EGFR inhibitors [11]. The anti-tumor properties of ALT have been shown to occur through a range of molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although some STAT3 inhibitors are undergoing clinical trials, none of the STAT3 inhibitors have been approved to date for the treatment of cancer . Accordingly, there is an urgent need to discover new drugs that can act as STAT3 inhibitors, either alone or in combination with the currently available anticancer drugs to address the unmet clinical need …”
Section: Introductionmentioning
confidence: 99%